2012
DOI: 10.1371/journal.pone.0049182
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-Ray Irradiation Effects of Li2O2, Li2CO3 and Li2O Revealed by Absorption Spectroscopy

Abstract: Li2O2, Li2CO3, and Li2O are three critical compounds in lithium-air and lithium-ion energy storage systems. Extensive measurements have been carried out to study the chemical species and their evolutions at difference stages of the device operation. While x-ray spectroscopy has been demonstrated to be one of the most powerful tools for such purpose, no systematic study on the irradiation effects have been reported. Here we carry out extensive time, position, and irradiation dependent Li K-edge soft x-ray absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
182
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(203 citation statements)
references
References 52 publications
20
182
1
Order By: Relevance
“…4C), and its fraction increases as a function of charge capacity. Additionally, the peak at around 530 eV is in good agreement with that of Li 2 O 2 (21 (24). In the literature for these layered materials, the changes in the spectra were mainly found in the early stage of charge, and these changes can be partly contributed by the oxidation of transition metals, as also observed in this study.…”
Section: +supporting
confidence: 88%
“…4C), and its fraction increases as a function of charge capacity. Additionally, the peak at around 530 eV is in good agreement with that of Li 2 O 2 (21 (24). In the literature for these layered materials, the changes in the spectra were mainly found in the early stage of charge, and these changes can be partly contributed by the oxidation of transition metals, as also observed in this study.…”
Section: +supporting
confidence: 88%
“…We have obtained images of the precipitate with different local O K-edge XANES spectra. By inspection of the spectra at different points of the images we concluded that locally rather pure phases of both Li 2 O 2 and Li 2 CO 3 coexisted, being the first in agreement with the literature [24], and the second with a commercial sample we measured. LiO 2 can only be hardly obtained in a pure The support is a carbonaceous inverse opal [23].…”
Section: Reference Samplessupporting
confidence: 88%
“…Qiao et al [24] specifically studied the effect of irradiating lithium peroxide, oxide, and carbonate with soft X-rays at room temperature. They found that carbonate and peroxide evolve toward oxide within several minutes of irradiation.…”
Section: Radiation Damagementioning
confidence: 99%
“…4b, the characteristic O K-edge peak associated with the Ni3d-O2p hybridization state is significantly degraded. In contrast, the intensity related to p*(C ¼ O) 41 experiences dramatic enhancement in the cycled electrode (red spectrum in Fig. 4b).…”
Section: Morphology and Electronic Structure Of Nio Nanosheetsmentioning
confidence: 93%